Hydroxychloroquine Induces Apoptosis in Cholangiocarcinoma via Reactive Oxygen Species Accumulation Induced by Autophagy Inhibition - Chen, Jiaqi; Pan, Qiaoya; Bai, Yang; Chen, Xuepeng; Zhou, Yi (Frontiers in Molecular Biosciences, 2021)
Purpose Despite considerable efforts to improve treatment modalities for cholangiocarcinoma, a common form of malignant tumor, its long-term survival rate remains poor. Hydroxychloroquine (HCQ) is a 4-aminoquinoline derivative antimalarial drug that has antimalarial and autophagy inhibition effects and exhibits comprehensive therapeutic effects on various cancers. In this study, we aimed to explore the anticancer potential and the underlying molecular mechanism of HCQ in cholangiocarcinoma treatment in vitro and in vivo. Methods Autophagy-related genes (ARGs) were obtained from the Human Autophagy Database and Molecular Signatures Database and the expression profiles of ARGs were downloaded from The Cancer Genome Atlas (TCGA) database. Different Expression Gene set were performed using R software. The GO and KEGG enrichment analysis were performed to reveal significantly enriched signaling pathways and to identify differentially expressed genes in cholangiocarcinoma tissues. HuCCT-1 and CCLP-1 cells were exposed to different concentrations of HCQ. Cell proliferation was detected by cell counting kit-8 (CCK-8), colony formation and 5-Ethynyl-2’- deoxyuridine (EdU) assays. Cell apoptosis and cycle arrest were detected by Live/Dead cell assay and flow cytometry (FCM). The inhibition of autophagy was observed using fluorescence microscopy. The reactive oxygen species (ROS) levels were assessed by fluorescence microscopy and FCM. The protein levels were determined by western blot. Cholangiocarcinoma cell line xenograft model was used to evaluate its antitumor activity of HCQ in vivo. Results Compared with normal tissues, there were 141 ARGs with an aberrant expression in cholangiocarcinoma tissues which were mainly enriched in autophagy-related processes. Inhibition of autophagy by HCQ effectively suppressed cholangiocarcinoma in vitro and in vivo. HCQ inhibited cell proliferation, induced apoptosis and cycle arrest in vitro by increasing ROS accumulation, which was involved in autophagy inhibition. ROS scavengers Reduced Glutathione distinctly weakened HCQ-induced cell apoptosis and viability inhibition in cholangiocarcinoma cells. In addition, HCQ inhibited growth of cholangiocarcinoma cell line xenograft tumors. Conclusion HCQ could inhibit cell proliferation and induce apoptosis in cholangiocarcinoma by triggering ROS accumulation via autophagy inhibition, which makes HCQ a potential antitumor drug candidate for cholangiocarcinoma treatment.